Dynamics of biofilm formation and the interaction between Candida albicans and methicillin-susceptible (MSSA) and -resistant Staphylococcus aureus (MRSA) - Zago, Chaiene Evelin (2015)
Polymicrobial biofilms are an understudied and a clinically relevant problem. This study evaluates the interaction between C. albicans, and methicillin- susceptible (MSSA) and resistant (MRSA) S. aureus growing in single- and dual-species biofilms. Single and dual species adhesion (90 min) and biofilms (12, 24, and 48 h) were evaluated by complementary methods: counting colony-forming units (CFU mL-1), XTT-reduction, and crystal violet staining (CV). The secretion of hydrolytic enzymes by the 48 h biofilms was also evaluated using fluorimetric kits. Scanning electron microscopy (SEM) was used to assess biofilm structure. The results from quantification assays were compared using two-way ANOVAs with Tukey post-hoc tests, while data from enzymatic activities were analyzed by one-way Welch-ANOVA followed by Games-Howell post hoc test ( = 0.05). C. albicans, MSSA and MRSA were able to adhere and to form biofilm in both single or mixed cultures. In general, all microorganisms in both growth conditions showed a gradual increase in the number of cells and metabolic activity over time, reaching peak values between 12 h and 48 h (<0.05). C. albicans single- and dual-biofilms had significantly higher total biomass values (<0.05) than single biofilms of bacteria. Except for single MRSA biofilms, all microorganisms in both growth conditions secreted proteinase and phospholipase-C. SEM images revealed extensive adherence of bacteria to hyphal elements of C. albicans. C. albicans, MSSA, and MRSA can co-exist in biofilms without antagonism and in an apparent synergistic effect, with bacteria cells preferentially associated to C. albicans hyphal forms.